Government Organization Adaptation to Implement Agile Practices in Provincial Smart City Agency - Rizki Wijaya; Wahyudi Kumorotomo; Ratminto Ratminto; Achmad Djunaedi (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to describe how the Provincial Smart-City Agency in Indonesia adapted agile practices. Implementing agile in conventional government is challenging because formal regulations dictate that a government entity operates by default. While agile approach demands a quick and effective response to shifting circumstances, its deployment frequently contrasts with the established bureaucracy. Considering practicing agile in government organizations, this paper asks how the Provincial Smart-City Agency adapts an agile approach to comply with the conventional government. This case study uses a qualitative method and NVivo software to organize and analyze data. Data were collected through internship observation from April to August 2022 and semi-structured interviews between June and September 2022. Data triangulation was used to validate the informants’ information. By describing the adaptation of agile practices in a provincial smart city agency, this paper expands knowledge on the adaptation of government organizations to implement agile concepts within a conventional bureaucracy that previous studies did not discuss. The result of this study contributes to agile adaptation practice to help government organizations start implementing agile practice by learning from the Provincial Smart-City Agency's success through six elements adapted to enable agility: the innovative structure of the organization, flexible working hours for non-permanent employees, workflow interaction, operational flexibility in the workplace, categorization of work into dynamic flexible tasks and routine repetitive tasks, and work location. These elements are affected by several factors, some of which arise from inherent characteristics of the agile components that influence the other components.